Chinese Herbal Medicine Combined With Antiepileptic Drugs for Intractable Epilepsy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zhao, Ying; Zhou, Hufang; Liu, Qingxuan; Liu, Jialin; Wu, Mengwei; Yuan, Siyuan; Xu, Weiwei; Wang, Ying; Wang, Kaiyue; Li, Lili; Liu, Jinmin (Frontiers in Pharmacology, 2022)
Background: Intractable epilepsy (IE) is still a major concern in neurology, and existing therapies do not adequately control symptoms. Chinese Herbal Medicine (CHM) has been widely used as an adjunct to antiepileptic drugs (AEDs) for IE. However, because of the contradictory findings reported in previous studies, it is uncertain if the present evidence is robust enough to warrant its usage. The purpose of this meta-analysis was to systematically evaluate the efficacy of the combination of CHM and AEDs for IE. Methods: From inception to September 2021, Medline, Ovid, Embase, Cochrane Library, Chinese Biomedical Database, China National Knowledge Infrastructure, VIP Database, and Wanfang Database were searched. Only randomized controlled trials (RCTs) that assessed the efficacy of the combination of CHM and AEDs for IE were included. We defined monthly seizure frequency as the primary outcome. The secondary outcomes included the abnormal rate of electroencephalogram (EEG), seizure duration, quality of life (QoL), and adverse events (AEs). Results: Twenty studies with 1,830 patients were enrolled. Most trials had poor methodological quality. The meta-analysis showed that the combination of CHM and AEDs was more efficient than AEDs alone in reducing monthly seizure frequency [MD = −1.26%, 95% CI (−1.62, −0.91); p < 0.00001], the abnormal rate of EEG [RR = 0.66%, 95% CI (0.53, 0.82); p = 0.0002], and improving the QoL [MD = 6.96%, 95% CI (3.44, 10.49); p = 0.0001]. There was no significant difference in seizure duration between groups. Moreover, the combination of CHM and AEDs significantly reduced the AEs [RR = 0.45%, 95% CI (0.32, 0.64); p < 0.00001]. Conclusion: The combination of CHM and AEDs could improve seizure control by reducing monthly seizure frequency and abnormal rate of EEG with a decreased risk of adverse events in patients with IE. However, these findings must be interpreted carefully due to the high or uncertain risk of bias in the included trials. To provide stronger evidence for the use of CHM combined with AEDs in IE, high-quality RCTs will be urgently warranted in the future.